PENGARUH IQ, MOTIVASI KERJA, REWARD, PUNISHMENT TERHADAP KEPUTUSAN MELAKUKAN PRAKTIK CREATIVE ACCOUNTING - Nur Rizky, Shinta; Wahyuni, Wiwin (SUSTAINABLE, 2024)
Knowing the influence of IQ, work motivation, reward and punishment on creative accounting practice decisions is the aim of this research. To obtain primary data, namely through a questionnaire with a measurement technique using a Likert scale. The population in this study were active accounting students at Wijaya Kusuma University, Surabaya. Samples were collected using purposive sampling techniques and calculated using the Slovin formula so that the total sample for this study was 73 respondents. Data was tested with multiple linear regression. Based on the research results, partial IQ variables, reward and punishment, work motivation have a positive effect on creative accounting practice decisions.